Global Burden, Trends, and Inequalities of Clostridioides difficile Infections from 1990 to 2021 and Projections to 2040: A Systematic Analysis - Zhihui Chen; Jing Wu; Xiangru Ye; Jialin Jin; Wenhong Zhang (Antibiotics, 2025)
Background: Clostridioides difficile infection (CDI) poses substantial clinical and economic challenges worldwide. This study aimed to evaluate the global burden, trends, and inequalities of CDI from 1990 to 2021, with projections extending to 2040. Methods: We conducted a systematic analysis of the Global Burden of Disease Study 2021 data for 204 countries and territories. CDI-related mortality and disability-adjusted life years (DALYs) were analyzed from 1990 to 2021. Joinpoint regression assessed the trends, a decomposition analysis identified the contributing factors, and cross-country inequalities were measured with slope and concentration indices. A log-linear age–period–cohort model projected future burden to 2040. Results: Global CDI-related deaths increased from 3047 (95% uncertainty interval [UI], 2550–3609) in 1990 to 15,598 (95% UI, 13,418–18,222) in 2021. The age-standardized mortality rate rose from 0.10 to 0.19/100,000 population (average annual percent change [AAPC], 2.26%; 95% confidence interval [CI], 1.77–2.76%), and the age-standardized DALY rate increased from 1.83 to 3.46/100,000 (AAPC, 1.94%; 95% CI, 1.43–2.45%). Epidemiological changes were the primary driver of this burden, contributing 45.46%. Inequalities were intensified, particularly in high sociodemographic index countries, evidenced by increases in the slope index from 2.00 to 4.17 and concentration index from 0.52 to 0.69. The projections suggest that mortality and DALY rates among populations aged ≥80 years will continue to rise through 2040. Conclusions: The global CDI burden has increased significantly over three decades, disproportionately affecting high sociodemographic index countries. The projected rise in CDI burden among older adults through 2040 underscores the urgent need for targeted interventions and strategic planning.